The Duty to Accomodate: Its Growing Impact on the Grievance Arbitration Process - Carter, Donald (Relations industrielles / Industrial Relations, 1997)
Grievance arbitrators now have a responsibility to interpret and apply human rights legislation in the course of resolving collective agreement disputes. This responsibility, however, raises the question of whether grievance arbitration is the most suitable forum for the application of human rights laws. In Canada, grievance arbitration has been a hybrid process, containing both public and private components. Recent arbitral jurisprudence, however, suggests that arbitrators see themselves as primarily private adjudicators. These cases indicate that arbitrators have been reluctant to give full scope to the duty to accommodate in order to avoid disturbing the terms of the collective agreement. This reluctance of the arbitrators to play a full role as human rights adjudicators means that, although arbitration is now a necessary forum for the resolution of human rights disputes, it is not necessarily the most ideal forum for the enforcement of Canadian human rights laws.